Service Needs for Corrections-Involved Parents With a History of Problematic Opioid Use: A Community Needs Assessment - Clark, Miriam; Kjellstrand, Jean; Morgan, Kaycee (Frontiers in Psychology, 2021)
The incarceration of a parent is often a continuation of a challenging family situation marked by poverty, unstable housing, trauma, and abuse. These challenges make it difficult for incarcerated parents reentering their communities to raise their children effectively and, thus, increase the likelihood of poor outcomes for their children. Children whose parents are also battling opioid misuse have an even higher risk for long-term problems. This study uses survey data from 48 community service providers to better understand the service needs of parents with histories of problematic opioid use who are reentering their communities after incarceration. Community service providers recommended implementing intervention programs that cover critical information related to basic needs, supportive community resources, drug treatment programs, and parenting to help individuals thrive in their communities and meet their children’s needs. The services most frequently identified by providers as important for reentering parents included housing, mentors or peer counselors, mental health support, group therapy and other support programs. Key topics to address in parenting programs included problem-solving techniques, the effect of parent’s addiction on children, and strategies for connecting with and meeting children’s needs. Suggestions are made for future research and intervention development.